Genetic and epigenetic regulation of phosphoinositide 3-kinase isoforms - Fyffe, C.; Buus, R.; Falasca, Marco (2013)
The last quarter of a century has witnessed remarkable progress in the understanding of phosphoinositide 3-kinases (PI3K) signalling and their involvement in different diseases such as cancer, diabetes and inflammation. Nevertheless, many questions remain open and among these the role of genetic and epigenetic regulation of PI3K isoforms is one of the most prominent. Emerging evidence Indicates that levels of isoforms can be modulated upon stimulation or in both physiological and pathological conditions including increased gene copy number and transcription regulation. In addition, an intriguing role for epigenetic regulation of PI3K expression, caused by mechanisms other than changes in the underlying DNA sequence, are starting to get appreciated. In this review, we summarize the genetic and epigenetic regulation of PI3Ks in physiology and the role played by their alterations in different diseases.